Analisis Prinsip Kerja Sama Pragmatik dalam Acara Komedi Lapor Pak! - Amilatus Sholikah; Mukhammad Aqmal Azis; Taswirul Afkar (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine the principle of cooperation in pragmatic analysis based on Grice's theory as applied in the Indonesian comedy show Lapor Pak! broadcast on Trans7. The focus of the research is on the violations of the maxims of quantity, quality, relevance, and manner as performed by characters such as Andika, Surya, Vincent, Wendy, and Kiki. These violations are analyzed as strategic communicative acts intended to generate humor. The study employs a qualitative descriptive method with listening and note-taking techniques applied to purposively selected dialogue transcripts. The findings reveal that the deliberate violations of Grice’s maxims function not as communicative failures, but as rhetorical and pragmatic tools that enhance comedic effect, deliver subtle social criticism, and strengthen character portrayal. Therefore, in the context of entertainment discourse, violating cooperative principles serves as an effective and purposeful pragmatic strategy.